PHARMACOECONOMIC ANALYSIS OF STATIN TABLETS - IN VITRO PERFORMANCE PERSPECTIVE - M, Vidyavathi; L, Koteswaramma; A, Krishnaveni; T, Madhuri; B, Sarada (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Pharmacoeconomics refers to the scientific discipline that compares the value of pharmaceutical drugs or drug therapies. The pharmacoeconomic analysis includes the research methods related to cost minimization, cost-effectiveness, and cost-benefit analysis. The present study concerned with the pharmacoeconomic analysis of statin tablets (simvastatin [S1-S5], atorvastatin [A1-A5], and rosuvastatin [R1-R5]) of different brands which are varying in their prices using in vitro evaluation methods of tablets. Methods: Weight variation, friability, hardness, disintegration, and dissolution tests of all selected statin tablets were performed as per official procedure for the pharmacoeconomic comparative analysis. Results: It was found the least T90% with S5 and high T90% with S1 tablets among simvastatin tablets, the least T90% was observed with A1 and A5 and high T90% with A2 tablets among atorvastatin tablets, and least T 90% was observed with R5 and high T90% with R2 was found among rosuvastatin tablets without any relation with their order of prices. Hence, the study concluded that there is no significant correlation between cost and in vitro performance as there is no excellent in vitro performance found from the costliest tablets and vice versa. Conclusion: The range of the cost of different marketed statin tablets is from Rs.17.5 to Rs.127.0 per a strip of 10 tablets. All brands of three drugs have equal strength which are assumed to produce the same outcomes. As there is no significant correlation between cost and results of some of in vitro parameters of the tablets, the cost minimization analysis can be ruled out for these brands of S1 to